Evaluating the efficacy of basiliximab versus no induction in low-immunological-risk kidney transplant recipients: a propensity score matched analysis - Dahao Zhang; Jiqiu Wen; Jianhui Dong; Rong Ma; Shijian Li; Jihua Wu; Ning Wen; Zhiying Lei; Haibin Li; Jun Yin; Xuyong Sun (Renal Failure)
Background The optimal use of induction therapy in low-immunological-risk kidney transplant recipients (KTRs) remains uncertain. While Basiliximab (BSX) is widely utilized, its comparative outcomes with no induction therapy require further evaluation.Method This single-center retrospective cohort study included 182 low-immunological-risk KTRs who underwent transplantation between January 2022 and March 2023. Patients were assigned to either no induction (n = 41) or BSX induction (n = 141) groups. Propensity score matching (PSM) minimized selection bias and controlled for confounding factors. Primary outcomes included the incidence of first acute rejection (AR) within 12 months, while secondary outcomes encompassed graft function, infection rates, and adverse events.Result After 12 months, the cumulative AR incidence was comparable between groups (p = 0.46). The no induction group demonstrated superior renal function, with consistently higher estimated glomerular filtration rates (eGFR) at early postoperative intervals. Additionally, this group exhibited reduced infection-related hospitalizations (respiratory infections: 7.32 vs. 29.1%, p = 0.008) and hematological complications (thrombocytopenia: 0.00% vs. 12.8%, p = 0.014). Mortality and graft loss rates were similar between groups.Conclusion In low-immunological-risk KTRs, no induction therapy achieves comparable AR prevention and renal function outcomes to BSX while reducing infection and hematological complications. These findings challenge the necessity of universal induction therapy in this population and support a personalized approach to immunosuppression protocols.